2010
DOI: 10.1124/dmd.110.034553
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Single Nucleotide Polymorphisms in CYP2A13 on Metabolism of 5-Methoxypsoralen

Abstract: ABSTRACT:A number of studies have demonstrated that cytochrome P450 (P450) converts furanocoumarin derivatives into reactive molecules, which form covalent bonds to biomolecules. 5-Methoxypsoralen (5-MOP) is a natural furanocoumarin from apiaceous plants. In this study, we examined the effect on 5-MOP metabolism of single nucleotide polymorphisms (SNPs) in CYP2A13. We used Escherichia coli-generated recombinant enzymes of wild-type CYP2A13*1 and five variants, CYP2A13*4 (R101Q), CYP2A13*5 (F453Y), CYP2A13*6 (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…This, together with the observation that phenobarbital and α-naphthoflavone induce 8-MOP metabolism in vivo and in vitro [36], suggest a role for P450s in 8-MOP metabolism, and an inhibitory effect of furanocoumarins on human CYP1A2 has recently been confirmed [21]. However, with the exception of the predominantly hepatic CYP2A6 [37], [38] and respiratory tract-specific CYP2A13 [23], [39], cutaneous P450s active in 8-MOP metabolism have not been characterised.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This, together with the observation that phenobarbital and α-naphthoflavone induce 8-MOP metabolism in vivo and in vitro [36], suggest a role for P450s in 8-MOP metabolism, and an inhibitory effect of furanocoumarins on human CYP1A2 has recently been confirmed [21]. However, with the exception of the predominantly hepatic CYP2A6 [37], [38] and respiratory tract-specific CYP2A13 [23], [39], cutaneous P450s active in 8-MOP metabolism have not been characterised.…”
Section: Discussionmentioning
confidence: 86%
“…P450s have been implicated in psoralen metabolism in insects [18], [19] and vertebrates [20], where different furanocoumarin derivatives induce or inhibit multiple P450s. In contrast, human P450s involved in 8-MOP metabolism have not been fully characterised, although furanocoumarins have been shown to inhibit human CYP1A2 [21] and CYP1B1 [22], polymorphisms in CYP2A13 shown to influence the metabolism of 5-methoxypsoralen [23] and the furanocoumarin chalepsin identified as both a substrate and inhibitor of coumarin hydroxylase ( CYP2A6 ) [24].…”
Section: Introductionmentioning
confidence: 99%
“…1C) compared with other CYP2A13 variants. Goto et al (2010) reported that the electrophoretic mobility of the recombinant CYP2A13*4 protein in SDS-polyacrylamide gel electrophoresis gel was slightly lower than the other recombinant CYP2A13 proteins. However, there was no obvious difference observed in electrophoretic mobility among the CYP2A13 variants in SDS-polyacrylamide gel electrophoresis analysis in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Some characteristics of the CYP2A13*4 enzyme have been clarified in previous reports, including a loss of P450 spectrum, low electrophoretic mobility, and an increased susceptibility to limited protein digestion Goto et al, 2010). However, the capacity of CYP2A13*4 to metabolize coumarin has not been characterized yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation